DNA-directed fabrication of NiCo2O4 nanoparticles on carbon nanotubes as electrodes for high-performance battery-like electrochemical capacitive energy storage device. (February 2019) - Xue, Yun; Chen, Tao; Song, Seunghyun; Kim, Pangil; Bae, Joonho
Abstract: In this work, deoxyribonucleic acid (DNA)-wrapped multi-walled carbon nanotubes (MWCNTs), denoted as CNT@DNA, were successfully assembled through a facile sonication treatment. By using the as-obtained CNT@DNA as template, a NiCo2 O4 -CNT@DNA composite with anchored NiCo2 O4 nanoparticles was fabricated by coating via in situ precipitation. The nanostructures of the as-synthesized samples were examined via powder X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Brunauer-Emmett-Teller (BET) techniques. Subsequently, the NiCo2 O4 -CNT@DNA and NiCo2 O4 -CNT (prepared without DNA) samples were used as cathode materials to fabricate supercapacitors with high capacitive performance. The results of electrochemical tests show that the NiCo2 O4 -CNT@DNA electrode exhibits a high specific capacitance of 760.0 F/g at 5 mV/s, which is higher than that of the NiCo2 O4 -CNT electrode. The NiCo2 O4 -CNT@DNA electrode displays a capacitance retention of 96.2% after 5000 cycles at the current density of 5 A/g. Moreover, a NiCo2 O4 -CNT@DNA//activated carbon (AC) asymmetric supercapacitor, prepared using NiCo2 O4 -CNT@DNA and activated carbon as the positive and negative electrodes, respectively, shows a specific capacitance of 223.7 F/g and a maximum energy density of 69.7 Wh/kg at a power density of 373.9 W/kg. The NiCo2 O4 -CNT@DNA//AC asymmetric supercapacitors, integrated in series, powered 5 mm red, yellow, and green light-emitting diodes (LEDs). The above results demonstrate that the novel NiCo2 O4 -CNT@DNA composites can be promising candidates as electrode materials for high-performance supercapacitors in future applications. Graphical abstract: Highlights: DNA-wrapped MWCNTs (CNT@DNA) are assembled through a facile sonication treatment. NiCo2 O4 nanoparticle-anchored composites NiCo2 O4 -CNT@DNA are fabricated through situ precipitation coating process. DNA plays a significant role in increasing the capacitance compared to NiCo2 O4 -CNT@DNA NiCo2 O4 -CNT electrodes. Supercapacitor based on battery-type NiCo2 O4 -CNT@DNA cathode and capacitor-type activated carbon anode exhibits excellent electrochemical performance with high energy density.